Magi 6 : the labyrinth of magic. - Otaka, Shinobu (VIZ Media, 2014)
"The furious battle between Ugo and Judar ends with the sudden appearance of Ren Kogyoku, Eighth Princess of the Kou Empire. The strange creatures she unleashes only drive home the point that Balbadd is surrounded by powerful enemies and further weakened by treachery from within. Sinbad has a plan to save Balbadd that will require strength and courage from everyone, particularly Alibaba, but no one doubts Alibaba more than himself" --